Duration of Resuscitation Efforts and Functional Outcome after Out-of-Hospital Cardiac Arrest: When Should We Change to Novel Therapies? - Reynolds, Joshua C. (2013)
BACKGROUND: Functionally favorable survival remains low after out-of-hospital cardiac arrest (OHCA). When initial interventions fail to achieve return of spontaneous circulation (ROSC), they are repeated with little incremental benefit. Patients without rapid ROSC do not typically survive with good functional outcome. Novel approaches to OHCA have yielded functionally favorable survival in patients who failed traditional measures, but the optimal transition point from traditional measures to novel therapies is ill defined. Our objective was to estimate the dynamic probability of survival and functional recovery as a function of resuscitation effort duration, in order to identify this transition point. METHODS AND RESULTS: Retrospective cohort study of a cardiac arrest database at a single site. We included 1,014 adult (≥18 years) patients suffering non-traumatic OHCA between 2005–2011, defined as receiving CPR or defibrillation from a professional provider. We stratified by functional outcome at hospital discharge (modified Rankin scale–mRS). Survival to hospital discharge was 11%, but only 6% had mRS 0–3. Within 16.1 minutes of CPR, 89.7% (95%CI: 80.3%, 95.8%) of patients with good functional outcome had achieved ROSC, and the probability of good functional recovery fell to 1%. Adjusting for prehospital and inpatient covariates, CPR duration (minutes) is independently associated with favorable functional status at hospital discharge (OR 0.84; 95%CI 0.72, 0.98;p=0.02). CONCLUSIONS: Probability of survival to hospital discharge with mRS 0–3 declines rapidly with each minute of CPR. Novel strategies should be tested early after cardiac arrest rather than after complete failure of traditional measures.